2023
DOI: 10.2174/1566523222666221004100858
|View full text |Cite
|
Sign up to set email alerts
|

Current Landscape and Emerging Opportunities of Gene Therapy with Non-viral Episomal Vectors

Abstract: Gene therapy has proven to be extremely beneficial in the management of a wide range of genetic disorders for which there are currently no or few effective treatments. Gene transfer vectors are very significant in the field of gene therapy. It is possible to attach a non-viral attachment vector to the donor cell chromosome instead of integrating it, eliminating the negative consequences of both viral and integrated vectors. It is a safe and optimal express vector for gene therapy because it does not cause any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Compared with plasmids, the use of a CssDNA vector has several advantages. First, in order to ensure safety and high-efficiency expression in host cells, plasmids must eliminate the unnecessary bacterial backbone sequences, which consists of elements necessary for the production in bacterial cells, such as antibiotic-resistance genes, and retain their active supercoiled conformation. , In contrast, CssDNA is generated without bacterial backbone sequences through the helper plasmid system and exists solely in a single topological structure. , Second, plasmid DNA can be recognized by the innate immune system causing gene silencing or elimination due to the presence of unmethylated CpG motifs, , whereas CssDNA may not be easily silenced and cleared with low immunogenicity. , Third, in combination with cationic lipids, the smaller size of CssDNA can facilitate nuclear translocation to enhance effects such as achieving a higher level of gene expression . Finally, CssDNA outperforms plasmid templates for gene writing because of its single-stranded feature. ,, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with plasmids, the use of a CssDNA vector has several advantages. First, in order to ensure safety and high-efficiency expression in host cells, plasmids must eliminate the unnecessary bacterial backbone sequences, which consists of elements necessary for the production in bacterial cells, such as antibiotic-resistance genes, and retain their active supercoiled conformation. , In contrast, CssDNA is generated without bacterial backbone sequences through the helper plasmid system and exists solely in a single topological structure. , Second, plasmid DNA can be recognized by the innate immune system causing gene silencing or elimination due to the presence of unmethylated CpG motifs, , whereas CssDNA may not be easily silenced and cleared with low immunogenicity. , Third, in combination with cationic lipids, the smaller size of CssDNA can facilitate nuclear translocation to enhance effects such as achieving a higher level of gene expression . Finally, CssDNA outperforms plasmid templates for gene writing because of its single-stranded feature. ,, …”
Section: Discussionmentioning
confidence: 99%
“…309,310 In contrast, CssDNA is generated without bacterial backbone sequences through the helper plasmid system and exists solely in a single topological structure. 15,129 Second, plasmid DNA can be recognized by the innate immune system causing gene silencing or elimination due to the presence of unmethylated CpG motifs, 311,312 whereas CssDNA may not be easily silenced and cleared with low immunogenicity. 15,252 Third, in combination with cationic lipids, the smaller size of CssDNA can facilitate nuclear translocation to enhance effects such as achieving a higher level of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the detection of blood concentration showed that 111In-IMP-288 could be rapidly absorbed into bone marrow without blood toxicity, which indicates that the combination of TF12 and 111In-IMP-288 May be applied to prostate treatment in the future [45][46][47][48][49]. In addition, the combination of TF12 and 111In-IMP-288 for treating metastatic colorectal cancer has entered the clinical phase I/II study.…”
Section: Tf12 Is Combined With 111in-imp-288mentioning
confidence: 99%
“…At the same time, the detection of blood concentration showed that 111In-IMP-288 could be rapidly absorbed into bone marrow without blood toxicity, which indicates that the combination of TF12 and 111In-IMP-288 May be applied to prostate treatment in the future [45][46][47][48][49]. In addition, the combination of TF12 and 111In-IMP-288 for treating metastatic colorectal cancer has entered the clinical phase I/II study.…”
Section: Tf12 Is Combined With 111in-imp-288mentioning
confidence: 99%